Bone. 3 : eyes of the storm - Smith, Jeff, 1960 February 27- (Bone, 2006)
Lucius, Smiley and Phoney are attacked by rat creatures in the forrest, barely making it to Lucius' tavern. At the farm, Fone Bone and Thorn are having strange dreams and Gran'ma Ben suddenly begins revealing long-kept secrets and new dangers.